Pengaruh Minat Dan Bakat Menggambar Terhadap Hasil Gambaran Siswa Kelas V Sd Muhammadiyah 24 Gajahan Tahun Ajaran 2015/2016 - Kurnia, Asti; , Drs. Suwarno, SH.,M.Pd (2016)
The purpose of this study are: (1) To determine the effect of interest in drawing on the results of an overview of students, (2) To determine the effect of talent to draw on the results of an overview of students, (3) To determine how much influence the interest and talent to draw on the results of a picture of students class V in 24 Gajahan SD Muhammadiyah Surakarta. This research is descriptive quantitative research with a conclusion through statistical analysis. Pengumpulkan techniques of data using questionnaires, observation and documentation. Data were analyzed using multiple linear regression analysis, t test, the coefficient of determination, SR and SE are preceded by analysis prerequisite test is a test of normality and linearity test. Results of data analysis obtained: (1) There is a positive influence on interest in drawing on the results of the student picture. Based on t testobtained t> t table, namely 4.364> 2.017 with significance value <0.05, ie 0,000 contributed by 71.3% relative and effective contribution of 42.3%. (2) There is a positive effect of talent to draw on the results of the student picture. Based on t test obtained t> t table, namely 4.297> 2.017 and the significance value <0.05, ie 0,000 contributed to relative 28.7% and the effective contribution of 16.9%. (3) There is a positive influence on the interests and talents of students to draw a picture of the results. Based on the multiple regression analysis results obtained Y = 4.491 + 0,473X_1 + 0,487X_2 Keywords: interest in drawing, drawing talent, the results overview.